Determination of effects of bacteria, mineral fertiliser and their combination on the plant growth of tulip (Tulipa gesneriana L.). (2017) - Ekinci, Melek; Dursun, Atilla; Kotan, Recep; Karagöz, Fazilet Parlakova; Kul, Raziye; Kazaz, Soner; Güneş, Adem
Using biofertiliser in agricultural production has increased lately, in this context; we investigated the effects of four bacteria isolates ( Paenibacilluspolymyxa -BI, Pseudomonas putida -BII, Bacillus subtilis -BIII and Kluyveracryocrescens -BIV) and 50% mineral fertilizer reduction with bacteria on plant growth of seven tulip cultivars. In the results, the effects of applications and cultivars were generally significant. With 1/2MF+BIII combination was ensured of shorter sprouting time. The bulb sprouting ratio was observed 97.33% (Jan Reus) and 99.78% (Parade) in varying proportions among the cultivars. The vegetation period had been longest with 1/2MF+BIII and American Dream cultivar. Treated applications showed the highest length and thickness of peduncle increased by 7.82% and 7.86% compared to control. The applications increased the plant height by 7.88% (BI) and the stem diameter by 6.06% (BIII) ratio. Dry matter in perianth increased by 6.30% with 1/2MF+BIV. As a result, the bacterial applications could be advised as fertiliser on plant growth of tulip.